Remote Ischemic Preconditioning Reduces Marathon-Induced Oxidative Stress and Decreases Liver and Heart Injury Markers in the Serum - Mieszkowski, Jan; Stankiewicz, Błaz∙ej; Kochanowicz, Andrzej; Niespodziński, Bartłomiej; Borkowska, Andz∙elika; Sikorska, Katarzyna; Daniłowicz-Szymanowicz, Ludmiła; Brzezińska, Paulina; Antosiewicz, Jędrzej (Frontiers in Physiology, 2021)
Clinical studies continue to provide evidence of organ protection by remote ischemic preconditioning (RIPC). However, there is lack of insight into impact of RIPC on exercise-induce changes in human organs’ function. We here aimed to elucidate the effects of 10-day RIPC training on marathon-induced changes in the levels of serum markers of oxidative stress, and liver and heart damage. The study involved 18 amateur runners taking part in a marathon. RIPC training was performed in the course of four cycles, by inflating and deflating a blood pressure cuff at 5-min intervals (RIPC group, n = 10); the control group underwent sham training (n = 8). The effects of RIPC on levels of oxidative stress, and liver and heart damage markers were investigated at rest after 10 consecutive days of training and after the marathon run. The 10-day RIPC training decreased the serum resting levels of CRP, ALT, GGT, and MDA. After the marathon run, CK-MB, LDH, cTn, AST, ALP, ALT, BIL-T, and MDA levels were increased and AKBR levels were decreased in all participants. The changes were significantly diminished in the RIPC group compared with the control group. The GGT activity remained constant in the RIPC group but significantly increased in the control group after the marathon run. In conclusion, the study provides evidence for a protective effect of RIPC against liver and heart damage induced by strenuous exercise, such as the marathon.